The impact of a viable myocardium on markers of left ventricular remodeling after an acute myocardial infarction - S.R. Kenjaev; U.R. Maxmudova; Ubaydullaeva Sh.M; Latipov N.M (Zien Journals, 2024)
Patients with AMI were investigated to determine the impact of a viable myocardial on LV remodeling characteristics. Study participants included 93 patients with an ST-segment elevation in acute coronary syndrome. Stress echocardiograms using dobutamine were performed on each subject.All patients had echocardiography and coronary angiography one and six months following coronary angioplasty. Patients with and without viable areas were split into two groups based on the outcomes of dobutamine stress echocardiography: group I had viable areas, while group II did not. Wall-motion score index, endsystolic volume index (ESVI), end-diastolic volume index (EDVI), and left ventricular ejection fraction (LVEF) were the metrics used to compare the two groups. Therefore, individuals with increasing left ventricular dilatation following reperfusion are distinguished from those with normal left ventricular geometry
Keywords: viable myocardium; remodeling; acute myocardial infarction; echocardiography